Chemical structure and biological properties of sulfated fucan from the sequential extraction of subAntarctic Lessonia sp (Phaeophyceae) - Leal, D.; Mansilla Muñoz, Andres Omar; Matsuhiro, B.; Moncada-Basualto, M.; Lapier, M.; Maya, J. D.; Olea-Azar, C.; De Borggraeve, W. M. (My University, 2018)
This work is related to the structural characterization of the sulfated polysaccharide from Lessonia sp and the study of its antioxidant and antiparasitic properties. Sequential extraction afforded D-mannitol as the only low MW sugar alcohol. Extraction with 2% CaCl2 afforded in 3.0% yield, a sulfated fucan (SF). Its major fraction (48.5% yield), isolated by ion-exchange chromatography corresponds to a linear polymer of alpha-L-fucopyranosil residues linked 1 -> 3, sulfated at the O-4 and partially at O-2 positions. By alkaline extraction, sodium alginate (10.3% yield) was obtained. The antioxidant capacity of SF by ESR showed high elimination index (IC50, mg/mL) of hydroxyl (0.27), alkoxy (10.05), and peroxyl (82.88) radicals in relation to commercial mannitol. SF showed activity against the epimastigote form of Trypanosoma cruzi parasite (250 mu g/mL) and low cytotoxicity in murine cells (367 mu g/mL). The elimination capacity of radicals in aqueous medium of SF would allow its potential biomedical application.
Keywords: fucoidan; sulfated fucan; antioxidant; antiparasitic; biological activities